Identification of reference genes for qRT-PCR in granulosa cells of healthy women and polycystic ovarian syndrome patients - Yue Lv (Nature Portfolio, 2017)
Abstract Comparative gene expression analysis by qRT-PCR is commonly used to detect differentially expressed genes in studies of PCOS pathology. Impaired GC function is strongly associated with PCOS pathogenesis, and a growing body of studies has been dedicated to identifying differentially expressed genes in GCs in PCOS patients and healthy women by qRT-PCR. It is necessary to validate the expression stability of the selected reference genes across the tested samples for target gene expression normalization. We examined the variability and stability of expression of the 15 commonly used reference genes in GCs from 44 PCOS patients and 45 healthy women using the GeNorm, BestKeeper, and NormFinder statistical algorithms. We combined the rankings of the three programs to produce a final ranking based on the geometric means of their stability scores. We found that HPRT1, RPLP0, and HMBS out of 15 examined commonly used reference genes are stably expressed in GCs in both controls and PCOS patients and can be used for normalization in gene expression profiling by qRT-PCR. Future gene-expression studies should consider using these reference genes in GCs in PCOS patients for more accurate quantitation of target gene expression and data interpretation.